2013
DOI: 10.1016/j.jiph.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metallo-β-lactamase NDM-1-producing multi-drug resistant bacteria at two Pakistani hospitals and implications for public health

Abstract: The results show a high level of NDM-1 positive organisms from variety of samples at both hospitals, implicating the spread of MBL genes in clinical isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 21 publications
2
31
1
Order By: Relevance
“…In a recent study from Islamabad, a prevalence of 23.6% for bla NDM-1 was reported in Gram-negative isolates where it was 13.4% P. aeruginosa and K. pneumoniae and 2% for E. coli. 21 Such difference in prevalence in present report might be due to small sample size. Also the previous report represented isolates from two cities.…”
contrasting
confidence: 58%
“…In a recent study from Islamabad, a prevalence of 23.6% for bla NDM-1 was reported in Gram-negative isolates where it was 13.4% P. aeruginosa and K. pneumoniae and 2% for E. coli. 21 Such difference in prevalence in present report might be due to small sample size. Also the previous report represented isolates from two cities.…”
contrasting
confidence: 58%
“…The few published prevalence reports on CRE in Pakistan are summarized in Table 3. CRE appears to be increasingly common in Pakistan (75,82,83), although notably, the laboratories of two of six hospitals contributing data to PARN did not isolate any CRE in their latest data sets in 2011 and 2012, respectively (Table 3) (75). The earliest report from a university hospital in Karachi showed that just 0.1% of clinical K. pneumoniae isolates were carbapenem resistant in the period between 2002 and 2007 (82).…”
Section: South Asiamentioning
confidence: 99%
“…As with India, CP-CRE have also been identified in different water sources in the environment since 2011 (87) and also in the community (15). The most common carbapenemase in Enterobacteriaceae in Pakistan remains NDM (83)(84)(85)(86)(87), although others, such as OXA, KPC, and IMP, have also been found in Enterobacteriaceae isolated from clinical specimens (88,89).…”
Section: South Asiamentioning
confidence: 99%
“…Carbapenemases belong to the A, B, and D molecular class of β-lactamases (41). Class A and D β-lactamases have a mechanism of serine-based hydrolysis, while class B β-lactamases are metallo-β-lactamases which have zinc in their active site (42). The carbapenemases group of class A contains members of the KPC, NMC, IMI, SME, and GES families.…”
Section: Hydrolyzing Antibiotics Iii: Carbapenemasesmentioning
confidence: 99%